PENGARUH PARTISIPASI ANGGARAN DAN KEJELASAN TUJUAN ANGGARAN TERHADAP KINERJA APARAT PEMERINTAH DAERAH KOTA MANADO - Tuerah, Raykes Hinrich; Morasa, Jenny (Universitas Sam Ratulangi, 2013)
Enactment of Law No. 32 of 2004 on regional government and Law No. 33 On financial balance between central and regional governments, bringing fundamental changes in the relationship Governance Government Relations and Finance, as well as bringing significant changes in the management of the Regional Budget. Budget and Expenditure ( Budget ) approach is based on performance. Clarity describes the breadth budget budget stated clearly and in detail, and understood by the parties responsible for its achievement.The purpose of this study was to determine the effect of budgetary goal characteristics include budgetary participation ( X1) and clarity of purpose budget ( X2) , the performance of government officials ( Y ) . While the object is examined in this study was 25 Unit ( SKPD ) in Manado City Government Environment.The study population was a Regional Working Units government Manado samples in this study were taken by using purposive sampling method obtained a sample of 60 respondents in the study by using multiple regression analysis and tested first by using the classical assumption and test the validity and reliability of data tool SPSS version 14.0.Characteristics of the test results budgetary purposes simultaneously have an influence on the performance of Manado city government. It is known to result Fhitung = 80.393 and F table = 2.37 and sig. 0,000 count <α: 5% ( 0.05) so that Ha is accepted. As for the partial test ( t test ) budget participation, budget goal clarity, feedback, evaluation and budget difficulties budgetary purposes a significant effect on performance. From the calculation ( PA ) t 2.697> 2.000 with significant ttable 0.009 <α: 5% ( 0.05) then H0 is rejected and Ha accepted means calculation ( KJA) t 2.541> 2.000 with significant ttable 0.014 <α: 5% ( 0.05) then H0 is rejected means that Ha is accepted. Based on the survey results revealed that the factors characteristic of the budget goal Budget Participation and Budget Clarity of purpose affect the performance of Manado City Government Officials. And suggestions for government officials in this study should be further studied using objective characteristics of the budget in order to guide, reference or benchmark for every budget.